Ssu72 phosphatase is a conserved telomere replication terminator - Escandell, Jose Miguel; Carvalho, Edison SM; Gallo‐Fernandez, Maria; Reis, Clara C; Matmati, Samah; Luís, Inês Matias; Abreu, Isabel A; Coulon, Stéphane; Ferreira, Miguel Godinho (The EMBO journal, 2019)
Telomeres, the protective ends of eukaryotic chromosomes, are replicated through concerted actions of conventional DNA polymerases and elongated by telomerase, but the regulation of this process is not fully understood. Telomere replication requires (Ctc1/Cdc13)‐Stn1‐Ten1, a telomeric ssDNA‐binding complex homologous to RPA. Here, we show that the evolutionarily conserved phosphatase Ssu72 is responsible for terminating the cycle of telomere replication in fission yeast. Ssu72 controls the recruitment of Stn1 to telomeres by regulating Stn1 phosphorylation at Ser74, a residue located within its conserved OB‐fold domain. Consequently, ssu72∆ mutants are defective in telomere replication and exhibit long 3′‐ssDNA overhangs, indicative of defective lagging‐strand DNA synthesis. We also show that hSSU72 regulates telomerase activation in human cells by controlling recruitment of hSTN1 to telomeres. These results reveal a previously unknown yet conserved role for the phosphatase SSU72, whereby this enzyme controls telomere homeostasis by activating lagging‐strand DNA synthesis, thus terminating the cycle of telomere replication. Synopsis The conserved (CTC1)‐Stn1‐Ten1 complex regulates DNA lagging strand synthesis and telomerase activity. CDK1‐dependent phosphorylation prevents Stn1 association with telomeres and is reversed by Ssu72 phosphatase, thereby allowing telomere overhang fill‐in reaction and consequently telomerase inhibition. A genome‐wide screen identifies Ssu72 as negative regulator of telomere elongation in fission yeast Ssu72 is required for semiconservative DNA replication by controlling Stn1‐Pol α interaction Ssu72 regulates Stn1 phosphorylation in fission yeast at a novel and highly conserved phosphorylation site located at the OB fold domain. The role of Ssu72 phosphatase in controlling telomere elongation via Stn1 recruitment is conserved in human cells. Graphical Abstract Reversal of inhibitory CDK phosphorylation on its Stn1 subunit allows (C)ST complex recruitment for telomeric DNA fill‐in synthesis in both fission yeast and human cells.